2015
DOI: 10.1371/journal.pone.0119831
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Prognostic Implications of Roundabout 4 (Robo4) in Adult Patients with Acute Myeloid Leukemia

Abstract: BackgroundRobo4 is involved in hematopoietic stem/progenitor cell homeostasis and essential for tumor angiogenesis. Expression of Robo4 was recently found in solid tumors and leukemia stem cells. However, the clinical implications of Robo4 expression in patients with acute myeloid leukemia (AML) remain unclear.MethodsWe investigated the clinical and prognostic relevance of mRNA expression of Robo4 in bone marrow (BM) mononuclear cells from 218 adult patients with de novo AML. We also performed immunohistochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…demonstrated, that Robo 4 was significantly upregulated in glioma tissues compared with normal brain tissue 28. Further total Robo 4 expression was significantly higher in bone marrow specimens of acute myeloid leukemia patients compared to normal bone marrow donors 30. These findings are in line with our observations in PCa tissue, where Robo 4 is higher expressed in cancerous tissue compared to normal prostate tissue, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…demonstrated, that Robo 4 was significantly upregulated in glioma tissues compared with normal brain tissue 28. Further total Robo 4 expression was significantly higher in bone marrow specimens of acute myeloid leukemia patients compared to normal bone marrow donors 30. These findings are in line with our observations in PCa tissue, where Robo 4 is higher expressed in cancerous tissue compared to normal prostate tissue, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…56 In addition, ROBO4 has recently been identified in murine HSCs 57,58 and human AML cells. 59 We found that HSCs and LSCs express ROBO4. Although CML LSCs expressed ROBO4 at high levels, AML LSCs expressed only low amounts of ROBO4.…”
Section: Discussionmentioning
confidence: 79%
“…Robo4 expression was initially detected in the vasculature at sites of active angiogenesis, including the placenta and various tumors [5]. Many subsequent studies have investigated Robo4 expression in physiological and pathological angiogenesis and revealed that Robo4 is involved in regulating angiogenesis during vascular development [31,49,108] in tumors [11,[109][110][111] and during ocular neovascularization [10,25,50,112,113].…”
Section: The Function Of Robo4 In Angiogenesismentioning
confidence: 99%
“…In addition to serving as an antiangiogenic target in carcinoma, Robo4 also functions as a biomarker for clinical characteristics and prognosis. Patients with acute myeloid leukemia (AML) presenting high Robo4 expression have a significantly shorter disease-free survival (DFS) and overall survival (OS) than patients with lower Robo4 expression [111]. However, increased Robo4 expression correlates with an increased OS of patients with non-small-cell lung cancer [131].…”
Section: Robo4 and Tumorsmentioning
confidence: 99%